Sudden Cardiac Death in Schizophrenia During Hospitalization: An Autopsy-Based Study - Chen, Yuanyuan; Zhang, Fu; Yan, Yanan; Wang, Shiquan; Zhang, Le; Yan, Fengping (Frontiers in Psychiatry, 2022)
Schizophrenia is a severe mental disorder that is often comorbid with heart dysfunction and even sudden cardiac death (SCD). Clinical studies of SCD in schizophrenia have been largely reported, while there are limited autopsy studies that directly showed whole-scale information of such events. In this study, we present nine autopsy-based SCD cases in schizophrenia patients who died suddenly during hospitalization. Their medical records before and during hospitalization, and postmortem autopsy findings were summarized. These decedents had an average duration of schizophrenia for 6.83±3.75 years with a male/female ratio of 4:5. They were all on intermittent antipsychotics medication before hospitalization and died within 15 days after hospitalization. Seven of the nine cases (77.8%) died of organic heart diseases such as severe coronary artery atherosclerosis (n=4), myocarditis (n=1), cardiomyopathy (n=1), and pulmonary thromboembolism (n=1). Two cases remained unexplained after systemic autopsy and toxicological examinations. Postmortem autopsy identified hepatic steatosis (n=6) and respiratory inflammation (n=3) as the most common associate extra-cardiac lesions. Our data provided autopsy-based data of SCD cases in schizophrenia and highlighted an intensive care of such patients during hospitalization.